L-Proline Catalysed Domino Reactions for the Synthesis of Heterocycles - Indumathi, Sethuraman; C. Menendez, Jose; Perumal, Subbu (Current Organic Chemistry, 2013)
L-Proline is a cheap, water-soluble organocatalyst that is able to induce the synthesis of a large number of heterocyclic systems. This work is reviewed, with emphasis on the literature of the 2005-2011 period. The domino reactions have been classified according to the nature of the first step of their proposed mechanisms, as follows: (i) iminium-initiated domino mechanisms; (ii) enamineinitiated domino mechanisms; (iii) reactions proceeding via the intermediacy of dienamines; (iv) reactions in which proline acts as a Lewis base and (v) L-proline/metal catalysed reactions.
Keywords: L-proline